KOMUNIKASI LEMBAGA UNTIRTA DALAM MERSPON UKM MAHASISWA (Studi Kasus: Adanya Aspirasi Lembaga UKM Dalam Ranah Fasilitas Dan Anggaran) - Silvi Aurelia; Andin Nesia (Universitas Sultan Ageng Tirtayasa, 2025)
Effective communication between university institutions and Student Activity Units (UKM) is crucial in ensuring transparency, openness, and responsiveness to student needs. This study aims to analyze the effectiveness of communication between the Academic Bureau, Student Affairs, and Cooperation (BAKK) of Sultan Ageng Tirtayasa University and UKM in conveying aspirations regarding facilities and budgets. This research employs a qualitative approach using a case study method, where data is collected through in-depth interviews with various UKM representatives and BAKK officials. The findings indicate that the communication process still faces several challenges, such as a lack of transparency in information, an imbalance in communication between BAKK and UKM, and delays in responding to student aspirations. Additionally, communication tends to be oneway, with UKM primarily receiving policies without actively participating in decision-making processes. In this context the Two-Way Symmetrical communication model is recommended to enhance the effectiveness of communication between both parties. This model emphasizes open dialogue, transparency, and active participation of UKM in campus policy formulation. By improving the communication system through increased transparency, better coordination, and clearer administrative mechanisms, the relationship between UKM and BAKK can become more harmonious and effective. This study also recommends regular discussion forums, the utilization of more advanced digital communication technology, and enhanced accountability in the management of UKM facilities and budgets.